Identification of Pathogens Causing Bulb Rot Disease on Garlic (Allium sativum L.) in Central Java, Indonesia - Lutfi Arifin; Siwi Indarti; Arif Wibowo (Jurnal Perlindungan Tanaman Indonesia, 2021)
Garlic bulb rot disease was found from garlics (Allium sativum L.) cultivated from 2017 to 2019 by farmers in Central Java Province, Indonesia. The initial symptoms of the disease were stunted, leaf yellowing, and necrotizing to rotten bulbs. This research was conducted to determine the major causal agent of garlic bulb rot disease in Central Java. A survey was carried out in five regencies across Central Java that were major garlic-producing areas. Nematodes were isolated using water immersion methode and pathogenic fungi were isolated on Potato Dextrose Agar (PDA). Nematode identification was carried out based on the Ditylenchus dipsaci morphological and morphometric character. Seven isolates of Fusarium species were obtained from infected garlic. Identification of four chosen isolates were performed by sequencing the TEF-1α gene. The TEF sequence of isolate TB3, KK1, and KK4 showed 99% similarity with several F. oxysporum, BT3 sequences showed 98% identity with several F. solani, and all were deposited in the NCBI GenBank. Three locations were positively infected by the interaction between D. dipsaci and Fusarium sp. Based on the results of the morphological identification, parasitic nematode was identified as D. dipsaci, while based on the morphological and molecular identification isolates Fusarium were identified as F. oxysporum and F. solani, respectively, as first report causal agents of garlic bulbs rot in Central Java.